Regresi Ridge Menggunakan Metode Dorugade untuk Memodelkan Kemisikinan di Jawa Barat - 10060119083, Dhea Hely Yulianti; Suliadi (Bandung Conference Series: Statistics, 2024)
Abstract. Linear regression analysis is a statistical method for forming a relationship model between a dependent variable and one or more independent variables. There are several assumptions that must be met in multiple linear regression, one of which is multicollinearity. One method to overcome multicollinearity problems is to use the ridge regression method. Dorugade (2016) developed a ridge parameter estimator for regression models based on the average MSE value which resulted in the Dorugade parameter estimator being able to overcome multicollinearity problems. This research applies that method to model the level of poverty in districts/cities in West Java in 2022 with the dependent variable poverty level and the independent variables gross regional domestic product, open unemployment, number of labor force, human development index, and average years of schooling. It was found that there was a multicollinearity problem and ridge regression using the Dorugade method was used. Obtained bias constant , the ridge equation model and the equation model . It is obtained that (number of labor force) is significan with negative effect on the poverty level. Abstrak. Analisis regresi linier adalah suatu metode statistika untuk membentuk model hubungan antara variabel dependent dengan satu atau lebih variabel independent. Ada beberapa asumsi yang harus terpenuhi dalam regresi linier berganda salah satunya adalah multikolinearitas. Salah satu metode untuk mengatasi masalah multikolinieritas adalah menggunakan metode regresi ridge. Dorugade (2016) mengembangkan estimator parameter Ridge pada model regresi berdasarkan nilai rata-rata MSE yang menghasilkan estimator parameter Dorugade mampu mengatasi masalah multikolinieritas. Skripsi ini menerapkan metode tersebut untuk memodelkan tingkat kemiskinan di Kabupaten/Kota di Jawa Barat Tahun 2022 dengan variabel dependent tingkat kemiskinan dan variabel independent produk domestik regional bruto, pengangguran terbuka, jumlah angkatan kerja, indeks pembangunan manusia, dan rata-rata lama sekolah. Pada pemeriksaan asumsi, diperoleh ada masalah multikolinieritas sehingga digunakan regresi ridge dengan metode dorugade. Diperoleh tetapan bias . Sehingga model persamaan ridge dan model persamaan . Diperoleh (jumlah angkatan kerja) yang signifikan. Dimana jumlah angkatan kerja berpengaruh negatif terhadap tingkat kemiskinan.